Hadith #493 - Sahih al-Bukhari - Yazid bin 'Abdul 'Aziz bin Siyah يزيد بن عبد العزيز بن سياه (Sahih al-Bukhari)
I used to accompany Salama bin Al-Akwa` and he used to pray behind the pillar which was near the place where the Qur’ans were kept. I said, “O Abu Muslim! I see you always seeking to pray behind this pillar.” He replied, “I saw Allah’s Messenger (ﷺ) always seeking to pray near that pillar.”
Grade: Sahih

Hadith #2840 - Sahih al-Bukhari - Yazid bin 'Abdul 'Aziz bin Siyah يزيد بن عبد العزيز بن سياه (Sahih al-Bukhari)
Salama said, “I gave the Pledge of allegiance (Al-Ridwan) to Allah’s Messenger (ﷺ) and then I moved to the shade of a tree. When the number of people around the Prophet (ﷺ) diminished, he said, ‘O Ibn Al-Akwa` ! Will you not give to me the pledge of Allegiance?’ I replied, ‘O Allah’s Messenger (ﷺ)! I have already given to you the pledge of Allegiance.’ He said, ‘Do it again.’ So I gave the pledge of allegiance for the second time.” I asked ‘O Abu Muslim! For what did
Grade: Sahih